Peran Guru Agama Kristen Dalam Penguatan Nilai Religius Siswa Dalam Lingkup Pendidikan di SDN 2 Sopai Kabupaten Toraja Utara - Weryanti Laen Langi' (Jurnal Keguruan dan Ilmu Pendidikan, 2022)
This study aims to determine the role of Christian Religious Education Teachers in increasing students' religious values ??within the scope of education at SD Negeri 2 Sopai. This type of research is descriptive qualitative. The subjects of this study were school principals, Christian religious education teachers and Catholic religious education teachers, as well as students of SD Negeri 2 Sopai. Data collection procedures through observation, interviews, documentation. Data analysis procedures, including data reduction, data presentation, data leveraging, and drawing conclusions. The results of the study indicate that SD Negeri 2 Sopai has a vision related to increasing students' religious values. Christian Religious Education Teachers and Catholic Religious Education Teachers have instilled Christian values ??according to indicators, namely the teacher as an interpreter of the Christian faith, the teacher being a shepherd and the teacher being a guide and leader. There are 3 (three) indicators regarding the role of Christian Religion Teachers related to strengthening students' religious values, namely: Praying, Reading the Word and Worshiping. It can be said that increasing religious values ??has been implemented by practicing based on each grade level, creating a “Bible Love Movement” program, and doing worship together whether it is worship on any predetermined days before learning. However, there is a solution that is applied in the interest of maintaining mutual tolerance between religious communities in students.